Avaliação das expectativas de auto-eficácia nos papéis da carreira: O Inventário de Crenças de Auto-Eficácia Relativamente aos Papéis da Carreira - Cardoso, Paulo (2010)
After the application of the Inventário de Crenças de Auto-eficácia Relativamente aos Papéis da Carreira (Vale 1997; ICARPC: Portuguese acronym for Self-Efficacy Beliefs Related to Career Roles Inventory) to a sample of 1005 Portuguese high school students, 488 grade 9 and 517 grade 12, the psychometric characteristics of ICARPC are analysed. The results confirm the ones obtained in previous research and support ICARPC’s reliability and validity. The practical implications of these findings concerning psychological intervention are discussed.